Enriching the historical meteorological information using Romanian language newspaper reports: A database from 1880 to 1900. (1st September 2020) - Cheval, S.; Haliuc, A.; Antonescu, B.; Tișcovschi, A.; Dobre, M.; Tătui, F.; Dumitrescu, A.; Manea, A.; Tudorache, G.; Irimescu, A.; Birsan, M.‐V.; Mock, C.
Abstract: Data recovery and climate reconstruction are an important support for climate change research, as they provide information from periods and areas with sparse meteorological networks. Various sources are currently in use for obtaining valuable evidence of past climate, such as ship logs, diaries, books, monastery documents. This study exploits newspaper reports in order to enrich the historical meteorological information over the territory of Romania, from the last two decades of the 19 th century. At that time, the area belonged to the Austro‐Hungarian Empire and Kingdom of Romania, and the meteorological services from Budapest (since 1870) and Bucharest (since 1884) were the providers of official meteorological information. The digital archive of three newspapers ( România Liberă, Gazeta de Transilvania and Foaia Poporului ) was investigated and the meteorological information was extracted and aggregated into a database containing 2, 132 unique entries clearly referenced in time and space. Each entry represents a meteorological event and several associated characteristics, such as date, location, impact and source. A verification procedure, consisting of comparisons with available measurements from the nearby weather stations and with a reanalysis dataset, was applied in order to validate the entries. The results show that the meteorological information was often present in the newspapers of the epoch. Some climatic features could be retrieved such as seasonality of extreme events, temperature and precipitation characteristics. This paper demonstrates the potential of the collected information to further enhance the understanding of climate change, impacts and climate perception at the end of the 19th century in Romania. Abstract : Screening the digital archives of three Romanian newspapers ( România Liberă, Gazeta de Transilvania and Foaia Poporului ) issued at the end of 19th century, we provide a high‐resolution, sub‐daily information of meteorological events and their characteristics for the interval spanning between 1880 and 1900. The spatial distribution of all phenomena (displayed in the figure above) mentioned in the newspaper reports show the abundance of meteorological evidence encrypted in this archive and highlight their potential for assisting detailed climate reconstruction in the time periods and area with sparse meteorological network.